ZMYND8 drives HER2 antibody resistance in breast cancer via lipid control of IL-27 - Yong Wang; Yanan Wang; Lei Bao; Goncalo Vale; Jeffrey G. McDonald; Yisheng Fang; Yan Peng; Ashwani Kumar; Chao Xing; Fara Brasó-Maristany; Aleix Prat; Carlos L. Arteaga; et al. (Nature Communications)
Abstract Anti-HER2 antibodies are effective but often lead to resistance in patients with HER2+ breast cancer. Here, we report an epigenetic crosstalk with aberrant glycerophospholipid metabolism and inflammation as a key resistance mechanism of anti-HER2 therapies in HER2+ breast cancer. Histone reader ZMYND8 specifically confers resistance to cancer cells against trastuzumab and/or pertuzumab. Mechanistically, ZMYND8 enhances cPLA2α expression in resistant tumor cells through inducing c-Myc. cPLA2α inactivates phosphatidylcholine-specific phospholipase C to inhibit phosphatidylcholine breakdown into diacylglycerol, which diminishes protein kinase C activity leading to interleukin-27 secretion. Supplementation with interleukin-27 protein counteracts cPLA2α loss to reinforce trastuzumab resistance in HER2+ tumor cells and patient-derived organoids. Upregulation of ZMYND8, c-Myc, cPLA2α, and IL-27 is prevalent in HER2+ breast cancer patients following HER2-targeted therapies. Targeting c-Myc or cPLA2α effectively overcomes anti-HER2 therapy resistance in patient-derived xenografts. Collectively, this study uncovers a druggable signaling cascade that drives resistance to HER2-targeted therapies in HER2+ breast cancer.